A new method of monitoring catheter-directed thrombolysis for deep venous thrombosis—application of D-dimer and fibrinogen testing. (April 2022) - Liu, Qiang; Chen, Wei; Wang, Yong-Li; Wang, Zheng-Yu; Peng, Zhi-Qing; Xiang, Jian-Feng; Chen, Liang; Pan, Yu-Cheng; Sha, Yan
Background: Catheter-directed thrombolysis (CDT) is one of the main treatment methods for acute deep venous thrombosis (DVT), which has the characteristics of long treatment time and large dosage of thrombolytic drugs. In the absence of good monitoring methods, problems such as low thrombolytic efficiency and high risk of bleeding are easy to occur. Objective: To evaluate the value of D-dimer (D-D) and fibrinogen (FIB) testing as a thrombolysis-monitoring method during CDT for acute DVT. Methods: Twenty patients with acute DVT were divided into group A and group B. During CDT, the D-D and FIB testing every 8 h were used in group A, and the venography and FIB testing every 24 h in group B. The thrombolysis rate, thrombolysis time, urokinase dosage, and X-ray radiation dose were compared. Results: The thrombolysis rate in group A was significantly higher than that in group B ( p < 0.05), but the number of venography and radiation dose were significantly lower than those in group B ( p < 0.05). Conclusion: D-D and FIB testing can improve the thrombolysis rate, reduce the risk of bleeding, and decrease the number of angiograms and X-ray radiation dose during CDT.